Penerapan Model ADDIE Pada Perancangan Permainan Ular Tangga Digital Berbasis Budaya Materi Bangun Datar - Rizkitania, Alifira; Arisetyawan, Andika (Didaktika, 2021)
This research focuses on designing a digital snake and ladder game that is integrated with Baduy culture on flat-shaped materials. This study uses two methods consisting of an ethnographic method used to obtain information about Baduy culture and the next method for designing digital learning media using the ADDIE model stage consisting of analysis, design, development, product testing, and evaluation activities. The research subjects used were 31 fourth-grade students of SDN Pasar Baru 1 Tangerang City. Data collection techniques used interviews, observations, questionnaires, and documentation studies. The results of the study based on the validation of media and material experts stated that the culture-based digital snake ladder game learning media was feasible to be used as a learning medium for fourth-grade students on flat-shaped materials. Student responses to culture-based digital snake and ladder game media make students interested in learning mathematics and culture. It can be concluded that the digital snake and ladder game media can be used as a distance learning solution so that students are not bored in learning mathematics. The culture-based digital snake and ladder game is a new alternative media that is fun, attracts students to learn mathematics as well as culturally, interactively, and innovatively.